SISTEM PENUNJANG KEPUTUSAN PENILAIAN PERILAKU KERJA PEGAWAI STUDI KASUS KANTOR DINAS PERINDAG POLMAN - Agustinus Sudi (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2021)
This study discusses the decision support system for evaluating employee work behavior carried out at the Polman Industry and Trade Office. Where, the current condition at the Polman Industry and Trade Service itself, the performance appraisal of its employees, especially non-permanent employees, is still done manually. This makes the need for a system that is able to manage employee performance appraisal data. This study aims to produce a system that can assist agency leaders as consideration in making employee research decisions. To minimize the obstacles faced, in this study apply the Analytic Hierarchy Process (AHP) method in a Decision Support System (DSS). The criteria used in this research are service orientation, integrity, commitment, discipline, cooperation and leadership. This system uses the Visual Basic Net 2010 programming language and Microsoft Office 2003 for the database.Keywords: support system, perindag, SPK, employees.